2017
DOI: 10.1001/jamaneurol.2017.0020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiovascular Risk Factors and Strokes in Younger Adults

Abstract: IMPORTANCE While stroke mortality rates have decreased substantially in the past 2 decades, this trend has been primarily limited to older adults. Increasing trends in stroke incidence and hospitalizations have been noted among younger adults, but there has been concern that this reflected improved diagnosis through an increased use of imaging rather than representing a real increase.OBJECTIVES To determine whether stroke hospitalization rates have continued to increase and to identify the prevalence of associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
245
2
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(264 citation statements)
references
References 20 publications
6
245
2
11
Order By: Relevance
“…We found that younger patients were at relatively increased odds of stroke after ILI compared to older patients; for every decade younger age, the odds increased by almost 10%. While the absolute risk of stroke is greater in older adults, approximately 10–14% of all strokes occur in people 18–45 years old, with the incidence and prevalence of stroke in the young increasing 4, 28, 29, 30, 31, 32, 33, 34. This increasing prevalence, moreover, coupled with greater heterogeneity in stroke etiology within the younger age group than in the older stroke population, presents a unique and vulnerable patient population where risk reduction efforts are of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that younger patients were at relatively increased odds of stroke after ILI compared to older patients; for every decade younger age, the odds increased by almost 10%. While the absolute risk of stroke is greater in older adults, approximately 10–14% of all strokes occur in people 18–45 years old, with the incidence and prevalence of stroke in the young increasing 4, 28, 29, 30, 31, 32, 33, 34. This increasing prevalence, moreover, coupled with greater heterogeneity in stroke etiology within the younger age group than in the older stroke population, presents a unique and vulnerable patient population where risk reduction efforts are of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional risk factors such as hypertension, diabetes, sedentary behavior, and smoking account for almost 80% of stroke risk, leaving a substantial proportion of stroke risk unexplained 4. In addition, conventional risk factors are primarily associated with long‐term risk and do not explain why individuals have strokes at one particular point in time rather than at another time.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, these findings have an impact on the stroke burden. A recent survey compared 362,339 stroke hospitalizations in 2003-2004 to 421,815 hospitalizations in 2011-2012 in the EUA, and found an absolute increase from 4% to 9% in the prevalence of obesity in among adults aged 18-64 years 20 . In a previous population-based study conducted in Joinville, we found that 16% (95%CI 14-19) of 601 patients with first-ever ischemic stroke were obese in the 2005-2006 period.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to a Finland cohort 22 but higher than those from Germany and China 23,24,25,26,27 . The causality between obesity and stroke is debatable 18,19,20 . A meta-analysis of 21 cohort studies reported that risk of ischemic stroke was 22% in patients who were overweight and 64% among those who were obese.…”
mentioning
confidence: 99%
“…Although costs for younger populations may be relatively low, they likely need care over a longer period of time, for the remainder of their lives for some patients. Stroke is also occurring at earlier ages in young adults 79 ; thus, further consideration of these caregiving needs is warranted.…”
Section: Limitationsmentioning
confidence: 99%